Ellipsometric characterization of inhomogeneous non‐stoichiometric silicon nitride films. (21st February 2013) - Nečas, David; Franta, Daniel; Ohlídal, Ivan; Poruba, Aleš; Wostrý, Petr
<x xml:space="preserve">Abstract</x> Variable‐angle spectroscopic ellipsometry is employed for the optical characterization of non‐stoichiometric silicon nitride thin films exhibiting inhomogeneity formed by refractive index and extinction index changes through the film thickness. For all the film samples, the best fit of the experimental data is achieved if, in addition to the inhomogeneity, an overlayer or roughness of the upper boundary is included. However, distinguishing of these two defects is found not to be possible. The influence of working gas ratio, deposition temperature and on/off time on the film properties is studied. The refractive index and extinction coefficient is found to increase with increasing working gas ratio and less significantly with decreasing deposition temperature. It is also found that the inhomogeneity increases with decreasing deposition temperature, and the deposition rate of the films decreases with increasing working gas ratio. The influence of the on/off time on the film properties is practically unimportant. Copyright © 2013 John Wiley & Sons, Ltd.